1990
DOI: 10.1172/jci114733
|View full text |Cite
|
Sign up to set email alerts
|

Elevated von Willebrand factor antigen is an early plasma predictor of acute lung injury in nonpulmonary sepsis syndrome.

Abstract: In this prospective study of 45 patients, we tested the hypothesis that markedly elevated levels of plasma von Willebrand antigen (vWf-Ag) a marker of endothelial cell injury, might predict the development of acute lung injury in patients with nonpulmonary sepsis syndrome. Acute lung injury was quantified on a four-point scoring system. At the time of entry into the study, none of the 45 patients had evidence of lung injury. Subsequently, 15 patients developed lung injury and 30 patients did not develop lung i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
135
1
10

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(154 citation statements)
references
References 32 publications
8
135
1
10
Order By: Relevance
“…Furthermore, plasma vWF-antigen levels were associated with the development of acute lung injury and 28-day survival. However, these data demonstrated moderate sensitivity (87%) and specificity (77%) (Rubin et al 1990;Sadler 1998). McGill et al (1998) also demonstrated that vWF might be useful to serve as prognostic marker, predicting survival with a positive predictive value by 80%.…”
Section: Von Willebrand Factor and Adamts13mentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, plasma vWF-antigen levels were associated with the development of acute lung injury and 28-day survival. However, these data demonstrated moderate sensitivity (87%) and specificity (77%) (Rubin et al 1990;Sadler 1998). McGill et al (1998) also demonstrated that vWF might be useful to serve as prognostic marker, predicting survival with a positive predictive value by 80%.…”
Section: Von Willebrand Factor and Adamts13mentioning
confidence: 94%
“…The hypothesis that vWF may be increased in patients suffering from ARDS vs. only septic patients could not be fulfilled. The same observation was done, when comparing sepsis vs. non-septic patients with hyperinflammation (Rubin et al 1990). Thus, it seems that vWF is a marker for diagnosing hyperinflammation, without being able to discriminate between specific organ damage (i.e.…”
Section: Von Willebrand Factor and Adamts13mentioning
confidence: 95%
“…O retorno da função endotelial às condições de normalidade, é acompanhado de redução dos níveis circulantes aos limites fisiológicos. A atividade antigênica plasmática do fvW (vWF:Ag) é portanto, considerada universalmente como um marcador de disfunção endotelial e assim utilizada em várias doenças [11][12][13][14][15][16] . Em pacientes com hipertensão arterial pulmonar, os sintomas aparecem em etapas onde já existe considerável dano à microcirculação naquele território.…”
Section: Resultados -Em 40 Pacientes Observamos Aumento Significativunclassified
“…Более эффективны ми вариантами диагностики являются компонен ты, описывающие взаимоотношения эндотелия, активации нейтрофилов и прокоагулянтного зве на системы гемостаза [43][44][45].…”
unclassified